Dampak Norma Sebaya pada Etika Bahasa: Systematic Literature Review - Partono Partono; Septi Susanti (Journal of Literature Review, 2026)
Abstract. This review aims to analyze the influence of peer norms on language ethics by examining how social normative frameworks and peer-based dynamics shape ethical language use across diverse communicative contexts. The method employed is a systematic literature review of scholarly articles addressing the impact of peer norms on ethical language practices. The literature search was conducted systematically through query transformation, screening based on inclusion and exclusion criteria, citation tracking, and ethical and contextual validation. A total of 50 selected articles were analyzed using qualitative thematic synthesis, grouping findings into five main areas: the influence of peer norms on language ethics, mediating mechanisms in ethical decision-making, differences between formal and informal contexts, the role of social identity and group affiliation, and theoretical contributions and implications for digital communication ethics. The findings indicate that peer norms exert a moderate to strong influence on ethical language behavior, with digital environments amplifying normative pressure through anonymity and group dynamics. These results highlight the complex interaction of norms, identity, and context in shaping language ethics and underscore the need for interdisciplinary approaches